Features of emotional burnout during the pandemic of nurses with different professional experience - V. V. Kozyreva (Вестник университета)
The article examines the phenomenon of emotional burnout in representatives whose work is carried out through the interaction of «person-person» in medical workers. In an emergency situation, medical workers are affected by a greater number of stressful factors than before, so the problem of emotional burnout, characteristic of all representatives of professions of a socionomic profile, becomes even more urgent. With the help of methods “Diagnostics of emotional burnout of personality” V.V. Boyko, “Study of the level of empathic tendencies” I.M. Yusupova, Spielberger-Khanin anxiety scale based on the results of mathematical analysis using the Mann-Whitney U-test, the relationship between the professional experience of nurses and the severity of the burnout syndrome is considered. In addition, a high correlation was found between the level of empathy among nurses and the severity of symptoms of emotional burnout. The relationship between the anxiety of nurses and the experience of professional activity has not been revealed. The results indicate that prevention is a necessary link in the fight against emotional burnout of nurses.